BUDAYA TABLIGH DI MEDIA SOSIAL: NILAI SPIRITUAL TERHADAP TABLIGH USTADZ HANAN ATTAKI DI MEDIA INSTAGRAM PADA GENERASI Z DI INDONESIA - Alanuari; Muhammad Syahrul Hasan; Fauziyah Hamidah (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
This research examines the impact of Ustadz Hanan Attaki's tablig on Instagram on the spirituality of Generation Z. This research uses a phenomenological culture approach to analyze Instagram as a new social media. Through content analysis of Instagram posts and an online survey involving 100 Generation Z respondents, this research explores how digital tabligh messages influence personal relationships with oneself, others, nature, and God. This study uses a qualitative descriptive method through a phenomenological cultur approach to understand how Generation Z interprets and internalizes the spiritual values ​​conveyed through digital tabligh. The findings show that social media, especially Instagram, plays a significant role in shaping the spiritual experiences and religious identities of young people in the digital era. This research contributes to new phenomenon culture regarding social media as part of religious communication and its impact on the spirituality of Generation Z in the digital era.